1995
DOI: 10.1002/hup.470100406
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mianserin hydrochloride on delirium

Abstract: Mianserin HCI (1&60 mg/day) was administered orally before bedtime to 46 patients (mean age: 63 years) with delirium at Kurume University Hospital. The therapeutic effects of mianserin were assessed pre-and post-treatment using the Delirium Rating Scale (DRS: Trzepacz et al., 1988). The mean pre-treatment DRS score was 21. This score decreased significantly (p <0-05) to 14 on treatment day 1 and 10 on day 3. Mianserin was observed to be effective in 85 per cent of the cases (marked improvement in 67 per cent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…However, in elderly patients neuroleptics frequently cause (1997) dangerous oversedation, severe extrapyramidal symptoms or activity and sleep disturbances. In this study, the clinical eectiveness of MS and the therapeutic plasma concentrations of mianserin were observed in the early stages of treatment, as has been observed for mianserin tablets (Nakamura et al, 1995). The prompt eect of mianserin against delirium contrasts with its delayed antidepressant eects.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…However, in elderly patients neuroleptics frequently cause (1997) dangerous oversedation, severe extrapyramidal symptoms or activity and sleep disturbances. In this study, the clinical eectiveness of MS and the therapeutic plasma concentrations of mianserin were observed in the early stages of treatment, as has been observed for mianserin tablets (Nakamura et al, 1995). The prompt eect of mianserin against delirium contrasts with its delayed antidepressant eects.…”
Section: Discussionsupporting
confidence: 65%
“…We have reported previously that mianserin, a tetracyclic compound, may eectively treat delirium in elderly patients as it has a rapid onset and few side-eects (Nakamura et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Nine of the 14 studies were single agent trials, [59][60][61][62][63][64][65][66][67] and 5 were comparison trials [68][69][70][71][72] (Table 1). Drugs used in single agent trials included haloperidol, 59 olanzapine, 60,61 risperidone, [62][63][64] and quetiapine.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Drugs used in single agent trials included haloperidol, 59 olanzapine, 60,61 risperidone, [62][63][64] and quetiapine. [65][66][67] Comparison trials included 1 with haloperidol, chlorpromazine and lorazepam 69 ; 1 with haloperidol and olanzapine 71 ; 1 with haloperidol and mianserin 68 ; and 2 with haloperidol and risperidone. 70,72 Patients were selected to participate in trials from a variety of populations.…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Melatonin supplementation has been postulated to be of benefit, [74] but supporting evidence is limited to a single case report [75]. Open studies of mianserin have reported efficacy comparable to haloperidol [38,39], with particular benefits for sleep-wake disturbances with few adverse effects [51]. A case series report suggested marked improvement in delirium symptoms, including sleep-wake disturbances in elderly patients administered trazodone [76].…”
Section: Adjunctive Agentsmentioning
confidence: 93%